WEBSITE-BASED RECOMMENDATIONS FOR TOURIST ATTRACTIONS IN BITUNG CITY USING CONTENT-BASED FILTERING ALGORITHMS - Tambajong, Karmel Daud; Rantung, Vivi Peggie (Informatika, Universitas Jenderal Soedirman, 2024)
This study aims to develop a website-based recommendation system for tourist attractions in Bitung City, leveraging content-based filtering algorithms. The primary goal of this research is to provide personalized recommendations to tourists, enhancing their travel experience by suggesting attractions that align with their preferences and interests. The methodology involves the implementation of a content-based filtering algorithm, which analyzes the attributes and features of various tourist spots to generate relevant recommendations. The system evaluates factors such as location, type of attraction, available facilities, and user reviews. The results indicate that the content-based filtering approach effectively identifies and suggests tourist attractions that match the users' interests, thereby improving the overall satisfaction of tourists visiting Bitung City. This recommendation system offers a practical solution for tourists seeking tailored travel experiences and contributes to the promotion of local tourism.